INVESTIGASI RISIKO KECELAKAN KERJA PADA PETERNAKAN SAPI X DI JAWA TIMUR DENGAN METODE HIRARC - Suprayogi, Dedy; Khoir, Ummul (VISIKES, 2025)
Risk management is a crucial aspect of Occupational Health and Safety (OHS) implementation at PT X, which operates in the livestock sector. The implementation of risk management in this company remains limited and has not been effectively operationalized. This research aims to provide a foundational step and evaluation material to minimize workplace accidents. The method used in this study is HIRARC, which is effective and efficient in identifying potential hazards, conducting risk assessments, and controlling risks. PT X comprises several departments with both minor and major hazard potentials. This study focuses on the Milking Department, which is vital in milk production. The assessment was conducted by analyzing all existing processes and activities results show that low risk accounts for 75%, medium risk for 25%, and high risk for 0%. Risk control is implemented through a hierarchy of controls. The application of this hierarchy of controls can minimize the existing risk levels. Overall, the implementation of OHS at PT X has not been optimal and requires further improvements as a foundational step in OHS implementation and evaluation, as well as to meet the requirements for the Occupational Health and Safety Management System (OHSMS) development.